EVALUASI KEPATUHAN PENGGUNAAN ALAT PELINDUNG DIRI (APD) PADA PEKERJA PROYEK PELEBARAN JALAN BATAS KOTA LUMAJANG – BATAS KAB. JEMBER - Subowo, Vincentia; Rahardjo, Boedi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to evaluate the level of compliance with the use of Personal Protective Equipment (PPE) as part of the implementation of Occupational Safety and Health (K3) in the Lumajang City Boundary–Jember Regency Boundary Road Widening Project. The study was conducted during industrial practice on June 16–August 1, 2025, using a descriptive quantitative approach. The research sample consisted of 37 workers directly involved in the Cement Treated Base (CTB) work and were selected purposively. Data collection was carried out through field observations, Likert scale questionnaires, interviews, and documentation, then analyzed using descriptive statistics in the form of percentage compliance levels. The results showed that most workers had used PPE according to standards so that the level of compliance was considered good. High compliance was supported by the implementation of safety mornings, toolbox meetings, and routine supervision by the Health, Safety, and Environment (HSE) team which was able to increase worker awareness and discipline towards work safety procedures. During the industrial practice period, no serious work accidents were found caused by negligence in the use of PPE, so the implementation of the Construction Safety Plan (RKK) was considered to have supported the achievement of the Zero Accident target. However, several challenges remain, such as discomfort when using PPE due to weather conditions, low worker discipline, and limited supervision in some work areas. Therefore, increased outreach, more intensive supervision, and the provision of more comfortable and standard-compliant PPE are recommended to improve the effectiveness of OHS implementation in construction project environments